ANALYSIS OF GAMES IN TEACHING FOREIGN LANGUAGE TO STUDENTS OF PRIMARY SCHOOL AGE AND LEARNING TO USE THEM IN THE COURSE OF THE LESSON - Shohida Ahmedova Akromjan kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article provides information about analyzing games and learning to use them in the course of teaching foreign languages to students of junior school age.